ANALISIS PENINGKATAN KESIAPAN DIRI MENJADI GURUMELALUI KEGIATAN BIMBINGAN DAN MOTIVASIMAHASISWA PROGRAM STUDI PENDIDIKAN AGAMA ISLAMDI STAI PUI MAJALENGKA - Hesya, Aay Farihah (Prodi PAI IAILM Suryalaya, 2018)
The struggle and sacrifice of teachers is not easy, in addition tobeing willing to provide knowledge and affection to their students,teachers are also required to increase their competence so that theybecome professional teachers. the teacher must be able to produceyoung people of high quality and noble character.This research has a purpose, they are: 1) To examine theincrease in self-readiness to become a teacher after participating in theactivities of guidance and motivation of students of Islamic religiouseducation courses, 2) To find out student responses regarding theguidance and motivation activities.This research is a qualitative research, carried out at STAI PUIMajalengka with the subject of Islamic Religious Education studyprogram students. The data analysis technique uses descriptive analysistechnique.In this regard, the authors make a hypothesis, namely: